Economic Development Of Batumi in 1888-1905 - Dumbadze, Khatuna (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2020)
Historical events, like the Porto-Franco regime, construction of the railway, and the reconstruction of the port hugely influenced the economic development of Batumi in the 80s of the XIX century. However, what played a huge role in this progress was the export of oil products. Russia, one of the world’s largest oil exporters since the 1980s, exports oil from Batumi to Baku. Oil export brought foreign capital and well-known industrialists: Rothschild, Mantashev, Tsovyanov, and others. Oil export-related enterprises were being built rapidly in Batumi, which naturally led to the development of the entire urban economy and population growth. Oil export determined the unprecedented progress of Batumi at the end of the 19th and the beginning of the 20th century. It became one of the large trade and industrial centers in the Caucasus after Baku and Tbilisi.